Fertilization Effects on Early Growth, Aboveground Biomass, Carbon Storage, and Leaf Characteristics of Eucalyptus pellita F. Muell. in South Sumatera - Wirabuana, Pandu Yudha Adi Putra; Sadono, Ronggo; Juniarso, Sergian (Jurnal Manajemen Hutan Tropika, 2019)
Fertilization is one of the nutrient management efforts that play an important role in improving the productivity of plantation forests. It was conducted to provide adequate nutrients for the plant at the initial growth period when the availability of soil nutrients is very limited. The optimum dose of fertilization for each plant is different depending on its requirement, climate, and soil properties. This study investigated the influence of fertilization on early growth, aboveground biomass, carbon storage, and leaf characteristics in Eucalyptus pellita in the sixth months after field establishment. An experiment comprising four treatments of fertilization, i.e., 0, 75, 133, and 167 kg ha -1 of triple superphosphate 46% P2O5 was set up using randomized complete block design with five replications. Four indicators were selected to evaluate the early growth of E. pellita, namely survival rate, height, the collar of diameter, and crown projection area. Aboveground biomass and carbon storage of E. pellita were estimated in each component, covering stem, bark, branches, and leaves. The leaf characteristics of E. pellita were described by individual leaf area, individual leaf dry weight, specific leaf area, and leaf area index. Results showed that the different treatment of fertilization did not have a meaningful effect on survival rate, individual leaf area, and specific leaf area. The treatments presented a substantial effect on other indicators such as height, diameter, crown projection area, aboveground biomass, carbon storage, individual leaf dry weight, and leaf area index. Despite the fact that the highest mean of height and collar of diameter were observed in the dose of 167 kg ha -1, the greatest average of aboveground biomass and carbon storage were noted in the rate of 133 kg ha -1. Nevertheless, this study did not find a highly different performance of E. pellita between both treatments statistically.